Sol–Gel Derived Alumina Particles for the Reinforcement of Copper Films on Brass Substrates - Samah Sasi Maoloud Mohamed; Marija M. Vuksanović; Dana G. Vasiljević-Radović; Ljiljana Janković Mandić; Radmila M. Jančić Heinneman; Aleksandar D. Marinković; Ivana O. Mladenović (Gels)
The aim of this study is to provide tailored alumina particles suitable for reinforcing the metal matrix film. The sol–gel method was chosen to prepare particles of submicron size and to control crystal structure by calcination. In this study, copper-based metal matrix composite (MMC) films are developed on brass substrates with different electrodeposition times and alumina concentrations. Scanning electron microscopy (FE-SEM) with energy-dispersive spectroscopy (EDS), TEM, and X-ray diffraction (XRD) were used to characterize the reinforcing phase. The MMC Cu-Al2O3 films were synthesized electrochemically using the co-electrodeposition method. Microstructural and topographical analyses of pure (alumina-free) Cu films and the Cu films with incorporated Al2O3 particles were performed using FE-SEM/EDS and AFM, respectively. Hardness and adhesion resistance were investigated using the Vickers microindentation test and evaluated by applying the Chen–Gao (C-G) mathematical model. The sessile drop method was used for measuring contact angles for water. The microhardness and adhesion of the MMC Cu-Al2O3 films are improved when Al2O3 is added. The concentration of alumina particles in the electrolyte correlates with an increase in absolute film hardness in the way that 1.0 wt.% of alumina in electrolytes results in a 9.96% increase compared to the pure copper film, and the improvement is maximal in the film obtained from electrolytes containing 3.0 wt.% alumina giving the film 2.128 GPa, a 134% hardness value of that of the pure copper film. The surface roughness of the MMC film increased from 2.8 to 6.9 times compared to the Cu film without particles. The decrease in the water contact angle of Cu films with incorporated alumina particles relative to the pure Cu films was from 84.94° to 58.78°.